The Role of Social Media in Promotion of Micro, Small and Medium Enterprises (MSMEs) and Its Implications Law Number 11 of 2008 Concerning Information and Electronic Transactions (UUITE) - Mas Try Washiludin Singapraja Manggala; Rendri Maulana; Denny Trias Saputra; Irma Rachmawati; Deden Sumantry; Murdiati Trisnaningsih (International Journal of Latin Notary, 2021)
The application of telematics applications (telecommunication, media and informatics) is one of the keys to support efforts to increase the competitiveness of the national industry. Currently, telematics is very easily accessible by entrepreneurs to improve their business competitiveness, including Micro, Small and Medium Enterprises (MSMEs). MSMEs use telematics services in the form of social media as a marketing tool to inform and offer products/services to consumers. MSME entrepreneurs choose social media for marketing to consumers online because this media is very easily accessible to both MSME actors and the general public. The purpose of this study is to examine the benefits of social media for MSME entrepreneurs and what are the implications for Law Number 11 of 2008 concerning Information and Electronic Transactions (UUITE). The research method uses a qualitative method, namely a descriptive approach to secondary data derived from literature, research journals, books, and websites that access the latest data information related to the use of social media and descriptive by utilizing secondary data derived from various literatures such as books, journals/articles and homepages to access the latest data and information related to the impact of social media in improving MSME business and its relation to the ITE Law. From the results of this study, it can be concluded that the use of social media is proven to increase sales of MSME products/goods and services and the ITE Law basically provides protection, security and data confidentiality during e-commerce transactions while also emphasizing responsibility to entrepreneurs as a result of event of failure in the function (malfunction) in the e-commerce system.